ANALYSIS OF THE QUALITY SERVICE ATM CARDLESS BPRS BHAKTI SUMEKAR PRAGAAN BRANCHES ON THE EFFECTIVENESS OF THE TRANSACTION - Cici Insiyah; L Mukarromah (Universitas Nahdlatul Ulama Sidoarjo, 2022)
The BPRS Bhakti Sumekar Pragaan branch provides the ATM cardless feature to assist customers in making independent transactions, so the quality of ATM cardless services is something that must always be considered to give satisfaction to customers when making separate transactions. This research was conducted to determine whether ATM cardless services can meet customer needs in independent transactions and to choose the customer's obstacles in using ATM cardless services. The research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation; technical triangulation will check the data's validity. The results showed that an ATM cardless service facility at the BPRS Bhakti Sumekar Pragaan branch greatly facilitated customers' cash withdrawal transactions. This was evidenced by the effects of interviews with seven customers who were met in the field; 6 customers expressed satisfaction with the ATM cardless service. The obstacles customers often find there are ATM errors and money-swallowing cases due to unstable network problems, so the BPRS Bhakti Sumekar Pragaan branch of BPRS Bhakti Sumekar continues to minimize them.